Electrochemical Aptasensors: Current Status and Future Perspectives - Abd-Elgawad Radi; Maha Ragaa Abd-Ellatief (Diagnostics, 2021)
This article reviews the progress of diversity of electrochemical aptasensor for target analytes detection. The immobilization strategies of aptamers on an electrode surface are addressed. The aptasensors are also introduced in compliance with the assay platforms. Many electrochemical aptasensors are nearly identical to conventional immunochemical approaches, sandwich and competition assays using electroactive signaling moieties. Others are “signal-on” and “sign-off” aptasensors credited to the target binding-induced conformational change of aptamers. Label-free aptasensors are also highlighted. Furthermore, the aptasensors applied for clinically important biomarkers are emphasized.